2021
DOI: 10.1038/s41586-021-03308-6
|View full text |Cite|
|
Sign up to set email alerts
|

A 20-year retrospective review of global aquaculture

Abstract: The sustainability of aquaculture has been debated intensely since 2000, when a review on the net contribution of aquaculture to world fish supplies was published in Nature. This paper reviews the developments in global aquaculture from 1997 to 2017, incorporating all industry sub-sectors and highlighting the integration of aquaculture in the global food system. Inland aquaculture-especially in Asia-has contributed the most to global production volumes and food security. Major gains have also occurred in aquac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
824
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,306 publications
(837 citation statements)
references
References 186 publications
7
824
0
6
Order By: Relevance
“…The replacement of FO with alternative oils, such as VO, in aquafeeds has become an extended practice in the aquafeed manufacturing industry and it is largely perceived as a way to guarantee the sustainable intensification of finfish aquaculture [ 11 , 36 , 37 , 38 ]. Along with diet optimisation, the identification of species that are capable of utilising the plant-based diets that are already dominating the market might be a valuable strategy for supporting the sustainability of aquaculture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replacement of FO with alternative oils, such as VO, in aquafeeds has become an extended practice in the aquafeed manufacturing industry and it is largely perceived as a way to guarantee the sustainable intensification of finfish aquaculture [ 11 , 36 , 37 , 38 ]. Along with diet optimisation, the identification of species that are capable of utilising the plant-based diets that are already dominating the market might be a valuable strategy for supporting the sustainability of aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…One particularly relevant aspect is the extensive use of fishmeal and fish oil (FO) in aquafeed formulations, with aquaculture being regarded to consume approximately 75% of the global production of these finite resources. Fishmeal and FO, derived to a large extent from capture fisheries, are being replaced by alternative ingredients, alleviating pressure on wild-fish stocks [ 11 ]. In this sense, vegetable oils (VO) are now commonly used ingredients in aquafeed formulations since, along with being readily available and inexpensive compared to FO, they are highly digestible and excellent sources of dietary energy [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is uncertainty on the global biomass of mesopelagic fishes, their role as biological carbon pumps is thought to have important implications for climate regulation, and the ecological impacts of harvesting them for aquaculture feed are unknown (Cavan et al, 2019;Hidalgo and Browman, 2019;Olsen et al, 2020). The aquaculture and feeds segments of the seafood industry have also taken substantial steps toward investing in research and development of feed alternatives like algae oil, genetically modified canola that contains high levels of omega-3 fatty acids, methane fermentation, and increased use of fisheries by-products (Cao et al, 2015;Pieja et al, 2017;Blasiak et al, 2018b;Cottrell et al, 2020;Naylor et al, 2021). The emergence of some of these feed alternatives creates challenging choices though, as GMOs remain controversial and agriculture is the leading cause of biodiversity loss on the planet (Brondizio et al, 2019).…”
Section: Taking a Systems Perspectivementioning
confidence: 99%
“…These GMO crops as well as algae oils represent two new alternatives to fish meal and fish oil, that could have special importance for aquaculture feeds (Cashion et al, 2017;Cottrell et al, 2020). All of these alternatives carry economic, environmental, nutritional, and ethical considerations (Pelletier et al, 2018), and intense efforts are underway to develop appropriate benchmark and certification criteria for aquaculture and feeds production and corresponding carbon footprints (Amundsen and Osmundsen, 2020;Osmundsen et al, 2020;Naylor et al, 2021).…”
Section: Sustainable Aquaculture Expansionmentioning
confidence: 99%
“…A recent global feed survey revealed that the annual growth of aquafeed production for 2018 was 4% [5], and was projected to reach 65 Mt in 2020 [6]. However, the inclusion rate of traditionally used finite and expensive marine protein and fat sources from wild-caught fish (i.e., fishmeal and fish oil) in the diets of farmed fish species will continue to decline and the industry has already shifted to crop-based ingredients to meet the rising demand for aquafeeds [2,6,7]. For instance, collective data from the Norwegian salmon (Salmo salar) industry reflect the change in modern aquaculture diet composition and confirm the reduced dependency on fishmeal derived from wild-caught fish; while in 1990 salmon diets consisted of 90% marine ingredients, already in 2013 their inclusion rate was less than 30%, which increased the share of plant protein sources to 37% [8].…”
Section: Introductionmentioning
confidence: 99%